Comprehensive analysis of the cerebellar vasculature of dromedary camels (Camelus dromedarius) - Ahmad Al Aiyan; Rinsha Balan (Frontiers in Veterinary Science)
The current study performed a comprehensive assessment of blood supply in the cerebellum of dromedary camels. To the best of our knowledge, this study is the first to provide detailed information about the origins, routes, and complicated patterns of branching in the rostral and caudal cerebellar arteries of dromedary camels. In total, 55 heads from male dromedary camels aged 2–6 years were analyzed using advanced casting techniques. Based on the specific challenges of this study, arterial structures were accurately evaluated using these strategic techniques. Rostral and caudal cerebellar arteries and branches of the basilar artery gave rise to multiple cortical branches categorized as hemispheric (lateral, middle, and medial) and vermian (paramedian and median) branches, which supply blood to the cerebellum. This novel anatomical knowledge can significantly improve our understanding about the neurovascular system of dromedary camels, thereby holding potential implications for veterinary diagnostics, treatment of neurological disorders, and comparative neuroanatomy research.